Decentralized Children's Immunization Record Management System for Private Healthcare in Malaysia Using IPFS and Blockchain - Hafidzah Halim, Faiqah; Aimuni Md Rashid, Nor; Farahin Mohd Johari, Nur; Amirul Hazim Abdul Rahman, Muhammad (Society of Visual Informatics, 2022)
In Malaysia, private healthcare providers keep computerized records of vaccination data, including personal information, diagnostic results, and vaccine prescriptions. However, such sensitive information is commonly stored using a centralized storage paradigm which subsequently brings about the issue of maintaining user privacy. Concerning this, unauthorized access to crucial information such as identity details and ailments that a patient is suffering from, as well as the misuse of patients' data and medical reports, are common threats to user's (patient) privacy. To overcome this problem, the researchers suggest leveraging IPFS (Interplanetary File System) and blockchain technology to create a decentralized children's immunization record management system. While respecting patient privacy, the proposed system also allows authorized entities, such as healthcare professionals, and provides easy access to medical data (e.g., doctors and nurses). The proposed decentralized system integrates IPFS, blockchain, and AES cryptography to ensure consistency, integrity, and accessibility. A permission Ethereum blockchain allows hospitals and patients within private healthcare providers to connect. We utilized a combination of symmetric and asymmetric key encryption to provide secure storage and selective records access. The proposed system was analyzed using Wireshark to evaluate the overall system's performance in terms of integrity and accessibility while sharing patient records. This project aims to provide automated system keeper using autonomous agents collaboratively with the role of blockchain for further enhancement.